Circular patch antenna using metamaterial / Mohamad Zharif Mohamad Zani - Mohamad Zani, Mohamad Zharif
This paper recommends a new technique of constructing circular antenna using metamaterial substrate. The study is concentrating on C-band frequency at 4.7GHz. The new small antenna has improved the performances in terms of directivity, gain, return loss and size. The size of metamaterial antenna is decreased by a factor 2.4. The directivity is increased from 4.17 for conventional antenna to 5.66 for metamaterial antenna. Better return loss also displayed from metamaterial antenna which is -24.2 dB. By analyzing the radiation pattern, the metamaterial antenna also focus to the supposed location. Result from the combination of material and structure on a single cell was led to the material with negative permittivity or metamaterial. The compact antenna is expected to improve features of conventional design by reducing the cost of production in correlation to the size reduction in mess production.